Alegorie Polski w gmachach publicznych i kościołach województwa śląskiego na wybranych przykładach (1922-1939): Allegories of Poland in the public buildings and the churches of the Silesian voivodeship on the basis of chosen examples (1922–1939) - Gorzelik, Jerzy (Artifex Novus, 2020)
Utworzenie autonomicznego województwa śląskiego w ramach polskiego państwa narodowego oraz diecezji katowickiej wiązało się z reorganizacją systemu władzy, w którym poczesne miejsce zajęły grupy polsko-śląskich duchownych oraz urzędników i świeckiej inteligencji. Ich wzajemna rywalizacja oraz wspólne dążenie do nacjonalizacji Górnoślązaków w duchu polskim inspirowały dwa odmienne, choć spokrewnione dyskursy, w których wykorzystywano środki obrazowe. Wśród nich znaczącą rolę odgrywały alegoryczne wizualizacje Polski, zakorzenione w tradycjach sztuki polskiej przełomu XIX/XX wieku. W wystrojach gmachów Sejmu Śląskiego i Śląskiego Urzędu Wojewódzkiego oraz starostwa powiatowego w Katowicach zastosowano motyw Polonia Triumphans. W pierwszym z przypadków rzeźbiarz Jan Raszka nadał personifikacji wczesnośredniowieczną stylizację, nawiązującą do piastowskiego „złotego wieku”, a u jej tronu umieścił asystę w osobach hutnika i górnika, stylizowanych na kresowych rycerzy. Inna z płaskorzeźb przedstawia Polonię jako Nike i Wolność prowadzącą do boju powstańca śląskiego, zobrazowanego jako hutnik z młotem, oraz żołnierza walczącego z Czechami o Śląsk Cieszyński. Wątek zbrojnej walki o granice pojawia się także w malowidłach Felicjana Szczęsnego Kowarskiego w budynku starostwa, gdzie ukazaną w postaci greckiej heroiny Polonię z mieczem i tarczą flankują postaci śląskich herosów – całość programu ma jawnie rewizjonistyczną wymowę. Wyraźnie większe bogactwo wątków prezentuje zespół trzech obrazów Józefa Unierzyskiego, zamówionych do kościoła mariackiego w Katowicach. Ich centralną postacią jest Maria Królowa Korony Polskiej, przybierająca cechy Polonii Triumphans. Fundamentem łączności Górnego Śląska z Polską jest tu wspólna katolicka wiara. Górnośląski lud pod przywództwem bliskich mu kapłanów włącza się u stóp Madonny w nurt polskiej historii, określony dziejową misją przedmurza chrześcijaństwa, wnosząc jako wiano żywą religijność i pracowitość. Na zlecenie proboszcza ks. Emila Szramka malarz zaprezentował zrastanie się z polskością jako naturalny i obustronnie korzystny proces. The creation of the autonomous Silesian voivodeship within the borders of the Polish nation state and of the Roman Catholic Diocese of Katowice meant a profound change in the distribution of power, the groups of Polish-Silesian clergy and Polish bureaucrats, as well as secular intelligentsia gaining increasingly in importance. Their rivalry and common effort to polonize Upper Silesians inspired two different, although interrelated discourses, visual means being involved in both of them. Among the motives, implemented in the propaganda, allegorical depictions of Poland - rooted in the traditions of the Polish art of the turn of the twentieth century – played a significant role. In the decorations of the edifices of Silesian Sejm and Silesian Voivodeship Office and of the county authorities they were shaped as the personification of Polonia Triumphans. In the former case the sculptor Jan Raszka represented the allegory as an early medieval figure, reminding of a „golden age” of the Piast dynasty, seated on the throne and accompanied by a coal miner and a foundry-worker, stylized as borderland knights. In another bas-relief Polonia was depicted as Victory and Liberty leading into battle a Polish-Silesian insurgent, rendered as a foundry-worker with a hammer in his hands, and a soldier, fighting against Czechs for Teschen Silesia. The strand of military fighting over disputed territories occurs also in the paintings by Felicjan Szczęsny Kowarski in the Katowice County Hall, where Polonia, depicted as a Greek heroine with a sword and a shield, is accompanied by Silesian heroes and the meaning of the decoration is manifestly revisionist, advocating moving Polish border westwards. A conspicuosly wider range of contents is reflected in a series of three paintings by Józef Unierzyski, ordered for St. Mary’s Church in Katowice. Their central figure is Mary the „Queen of the Polish Crown”, assuming the features of Polonia Triumphans. The connection between Upper Silesia and Poland is founded here on the common catholic faith. At the feet of Madonna Upper Silesian folk, led by clergy, that remains faithfull to its popular roots, and bringing its vivid religiosity and dilligence, joins the stream of the Polish history, determined by the historical mission of antemurale christianitatis,. Commissioned by the parson Emil Szramek, the painter represented the growing together of Upper Silesia and Poland as a natural and mutually profitable process.